If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(4y+2)-12=-8(y+4)+4y
We move all terms to the left:
-3(4y+2)-12-(-8(y+4)+4y)=0
We multiply parentheses
-12y-(-8(y+4)+4y)-6-12=0
We calculate terms in parentheses: -(-8(y+4)+4y), so:We add all the numbers together, and all the variables
-8(y+4)+4y
We add all the numbers together, and all the variables
4y-8(y+4)
We multiply parentheses
4y-8y-32
We add all the numbers together, and all the variables
-4y-32
Back to the equation:
-(-4y-32)
-12y-(-4y-32)-18=0
We get rid of parentheses
-12y+4y+32-18=0
We add all the numbers together, and all the variables
-8y+14=0
We move all terms containing y to the left, all other terms to the right
-8y=-14
y=-14/-8
y=1+3/4
| -2(q-5)=-4 | | .5=(c-8) | | 5.2g+10=3.2g+22 | | -2x-5=-4x+ | | 2x+-4=30 | | 160+0.30x=80+0.40x | | -6x-43=-4x-2 | | 6•7x-20=6x | | p/4 + 14 = 15 | | 160+0.30x=80+0.40 | | -2(z-7)=-8 | | 9(x+11)=18 | | 3/4c=- | | 7•7x-20=6x | | p4 + 14 = 15 | | 3(d+1)+4=19 | | 0=-16t^2+47t-30 | | 9−(6−8x)=4x+5 | | 3(2x-6)=2(3x-4) | | -8-8b=-10b | | 4+x=41 | | 130+0.60x=50+0.80x | | 3u+39=-2(u+3) | | -2t^2+13t-15=-(t-5)(2t-3) | | 49y=6(8y+6) | | 49-11x=11+8x | | 130+0.60x=50+0.80 | | (5x-3)/(x+8)=0 | | 4x^+12=3x^+13 | | -5(3x-2)=3(1-4x)+12 | | 2g+3=6-13 | | -2+2y=10 |